Radiation complex on the basis of helium ions linac - Dubniuk, S.N.; Anokhin, R.A.; Dyachenko, A.F.; Коbets, А.P.; Kravchenko, A.I.; Manuilenko, O.V; Pavlii, К.V.; Reshetnikov, V.N.; Shevchenko, A.S.; Soshenkо, V.A.; Tishkin, S.S.; Zajtsev, B.V.; et al. (Вопросы атомной науки и техники, 2018)
The numerical simulation results and experimental investigation of helium ions linear accelerator with output energy 4 MeV and focusing by an RF field are presented. The variant of alternating-phase focusing with a step change in the synchronous phase and increasing amplitude of the RF field in accelerating gaps in the grouping section of the accelerating-focusing tract of the accelerator is used to ensure the radial-phase stability of the accelerated beam. The methods for increasing the accelerated ion beam current, as well as the beam current density on the target, are considered.